Jappy's kitchen a business plan for small scale production of empanada - Hidalgo, Jan Isobel C. (2010)
The best of businesses are those with heart and grow roots, enterprises that touch every consumer and connect with them individually at a level of closeness that creates a bond which harbours pride and familiarity which keeps them from coming back, such businesses stay and make their mark in whatever industry they choose tom stand out. Food is something that never goes out of style in general, the challenge has always been to tailor fit it to match the fast paced change of human needs and covered comforts. Jappy?s Kitchen as a company endeavors to do just that. The company is a homegrown business owned and managed by the very person who started it all, Mr. Joel M. Hidalgo with the support and help of the entire family. The establishment intends to start small, for big things always come in small packages. The company will start a small shop along the Malaybalay City, Bukidnon Sayre Highway ready to serve the weary and the hungry alike, offering Mr. Hidalgo?s classic specially EMPANADA and other food stuff with a special touch of home goodness. The company shop located at the hub-hub of the city, offers to cater to both young and old since it is both fun and healthy; the sophisticated and meagre for its delectability yet familiarity; the weary and hungry for it is both comforting satisfying. The empanada making business which started out as a hobby and special favor to friends and relatives of the Hidalgo family, grew into a full in-house profit business way back in 1990 up until 2003 when the family business changed course to photocopying. But good food has never ceased to exist in the household. Today as a daughter endeavors to finish a course in food technology, the family sees it fitting to revive a business loyally anticipated by an established clientele, who have never ceased to look forward for its mass production since 2003. Now armoured with the right arsenal, a good business plan and a good sales projection from a 5-day Test Sale, the company is sure that the business will be a success, starting with a Php 100,000 personal start up capital and a Php 250,000 bank loan, which the company foresees to pay in less than a year. The loan mainly shall be used for product improvement and production, basically to add to the company start up capital. The company though starting with a small shop to cater for the residents of the urban parts of Malaybalay city, by offering a not so quintessential service. The product shall be sold in a shop/deli/café/mini-library rolled into one and soon intends to expand by putting up stalls in major hotspots in the city and expand further, taking baby steps at a time. How do we know we will succeed? We are aware that food in general is essential and yet we understand too that it is a fad and a trend that never quite goes out of style but morphs as the time changes in this fast paced life of ours. Knowing such fact is an edge enough, yet we know the secret just how to morph our business to fit the times
Thesis (BS Food Technology) -- University of the Philippines Mindanao, 2010
Keywords: Empanada; Business plan